Present bias and financial behavior. Issue 2 (23rd July 2019) - Xiao, Jing Jian; Porto, Nilton
Abstract: Present bias is an important term in the theory of self‐control in behavioral finance. Empirical research finds that present bias is associated with undesirable spending, borrowing, and saving behaviors. Unlike previous research that focuses on one domain of financial behavior, the purpose of this study is to examine associations between present bias and a set of financial behaviors in various domains: spending, borrowing, saving, and money management. With data from a national urban sample in China, results show that some behavioral patterns are consistent with theoretical predictions that present biased consumers are more likely to spend in the present and less likely to save for the future. The findings have implications for further research on present bias and help researchers better understand this important concept. The results are also informative for financial planners to better serve their clients.